Neighbourhoods for the city in Pacific Asia - Ho, Kong-Chong, 1955- (Amsterdam : Amsterdam University Press, 2020)
The largest cities in East Asia are the engines of their countries' economic growth, seats of national and regional political power, and repositories of the nation's culture and heritage. The economic changes impacting large cities interact with political forces along with social-cultural concerns, and in the process also impact the neighbourhoods of the city. My study looks at local collective action and city government responses and its impact on the community and the city. By adopting a multi-sited comparative approach in studying local action in five important cities (Bangkok, Hong Kong, Seoul, Singapore and Taipei) in Pacific Asia, the book enables comparisons across a number of key issues confronting the city: heritage (Bangkok and Taipei), community involved provisioning of amenities in a number of different contexts (Hong Kong, Seoul, Singapore), place making versus place marketing (Hong Kong). The collaborative efforts city governments establish with local communities becomes an important way to address the liveability of cities.
Frontmatter -- Table of Contents -- Preface -- Acknowledgements -- 1. Neighbourhoods for the City -- 2. The Political Economy of Cities in Pacific Asia -- 3. The Logic of Comparisons in Multi- Sited Research Designs -- 4. Sungmisan: The Power of Village Social Enterprises -- 5. Mahakan: Neighbourhood Heritage Curation Attempts -- 6. Tangbu: Saving the Old Sugar Warehouses -- 7. Langham Place: Mega Project-Led Inner-City Regeneration -- 8. Tampines Central: Government- Resident Partnerships at Work -- 9. Neighbourhood Action, Metropolitan Politics, and City Building -- Index
Online resource; title from digital title page (viewed on August 06, 2020).
Added to collection customer.56279.3
Keywords: Cities and towns -- East Asia; Neighborhoods -- East Asia; Cities and towns; Neighborhoods; East Asia; East Asia, neighbourhood action, city government, sociable amenities; Electronic books